2014
DOI: 10.1007/s00018-014-1722-0
|View full text |Cite
|
Sign up to set email alerts
|

The FHIT gene product: tumor suppressor and genome “caretaker”

Abstract: The FHIT gene at FRA3B is one of the earliest and most frequently altered genes in the majority of human cancers. It was recently discovered that the FHIT gene is not the most fragile locus in epithelial cells, the cell of origin for most Fhit negative cancers, eroding support for past claims that deletions at this locus are simply passenger events that are carried along in expanding cancer clones, due to extreme vulnerability to DNA damage rather than to loss of FHIT function. Indeed, recent reports have reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
86
0
5

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 89 publications
(96 citation statements)
references
References 69 publications
5
86
0
5
Order By: Relevance
“…In line with our hypothesis, we found that Fhit − / − mice showed significantly more carcinogen‐induced tumors than wt mice ( P  <   0.001). We expect that the skin of Fhit − / − mice treated with the DMBA/PMA induction protocol would also display increased single‐base substitutions, copy number alterations and aneuploidy, representative of the genome instability seen in Fhit knockout mice 25, 39, compared to the skin of the similarly treated control mice.…”
Section: Discussionmentioning
confidence: 99%
“…In line with our hypothesis, we found that Fhit − / − mice showed significantly more carcinogen‐induced tumors than wt mice ( P  <   0.001). We expect that the skin of Fhit − / − mice treated with the DMBA/PMA induction protocol would also display increased single‐base substitutions, copy number alterations and aneuploidy, representative of the genome instability seen in Fhit knockout mice 25, 39, compared to the skin of the similarly treated control mice.…”
Section: Discussionmentioning
confidence: 99%
“…Fhit knockout mouse models are much more susceptible to develop both spontaneous and carcinogen-induced tumors than wild-type control mice [16, 52]. As a tumor suppressor, FHIT’s role in the DDR is mainly guarding genome integrity and regulating apoptosis (reviewed in [23]). Pioneering work by the Huebner group showed that FHIT protects genomic integrity by preventing spontaneous replication stress.…”
Section: Cfs Gene Products With Roles In the Ddrmentioning
confidence: 99%
“…Hemizygous deletions are frequent in CFS genes (CFS-Gs), suggesting that these genes are haploinsufficient [16, 17] or that the second allele could be epigenetically silenced, as is seen for many CFS-Gs [18–22]. Furthermore, emerging findings show that CFS-Ps are directly involved in the DNA damage response (DDR) and therefore participate in maintaining genomic integrity (reviewed in [2325]). These studies reveal that expression and activity of several CFS-Ps are induced in response to DNA damage and contribute to proper cellular checkpoint response, including DNA repair, cell cycle arrest, and apoptosis ([24, 26] and sections below).…”
Section: Introductionmentioning
confidence: 99%
“…The fragile histidine triad (FHIT) is a tumor suppressor gene and is located in FRA3B which is the most active common fragile site, where DNA damage leading to aberrant transcripts and translocations frequently occur [1][2][3][4][5]. Abnormal transcripts of FHIT have been detected in various types of cancer [6,7].…”
Section: Introductionmentioning
confidence: 99%